A polymorphism (rs1042522) in TP53 gene is a risk factor for Down Syndrome in Sicilian mothers. (17th November 2017) - Salemi, Michele; Barone, Concetta; Salluzzo, Maria Grazia; Giambirtone, Mariaconcetta; Scillato, Francesco; Galati Rando, Rosanna; Romano, Carmelo; Morale, Maria Concetta; Ridolfo, Federico; Romano, Corrado
Abstract: Objective: Trisomy 21 is the most frequent genetic cause of intellectual disability. Tumor Protein 53 ( TP53 ) gene down-regulation triggers chromosomal instability. A TP53 gene polymorphism c.215G > C (rs1042522) is associated with accumulation of aneuploid cells. We analyzed the TP53 c.215G > C (rs1042522) polymorphism in Sicilian mothers of subjects with Down Syndrome (DS) within a case-control study. Methods: Nucleotide polymorphism was detected by pyrosequencing technology. Results: The distribution of TP53 c.215G > C polymorphism showed significant difference between mothers of subjects with DS and controls. Conclusions: Our data show that TP53 c.215G > C polymorphism is a risk factor for DS in Sicilian mothers.